2013
DOI: 10.1144/jmpaleo2012-010
|View full text |Cite
|
Sign up to set email alerts
|

Living benthic foraminifera: biogeographical distributions and the significance of rare morphospecies

Abstract: Abstract. Previous studies have investigated regional distribution but this is the first attempt to investigate the global biogeographical distribution of individual morphospecies of living/stained smaller benthic foraminifera. From 8032 samples collected between 1952 and 2011 data have been gathered on the relative abundance of >120 species in five major environments ranging from marsh to deep sea. There is a spectrum of six groups of species with abundance ranging from very high (Group 1) to extremely low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 166 publications
(225 reference statements)
4
20
0
Order By: Relevance
“…, Goldstein, 1988, Patterson, 1990, Murray, 2013. The high relative abundance of a small number of taxa, irrespective of overall diversity, is consistent with previous estuarine foraminifera studies (Murray, 2013). The spatial distribution of the two assemblages within the lagoon, with a duospecific assemblage in deeper water and a more diverse shallow water assemblage, is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…, Goldstein, 1988, Patterson, 1990, Murray, 2013. The high relative abundance of a small number of taxa, irrespective of overall diversity, is consistent with previous estuarine foraminifera studies (Murray, 2013). The spatial distribution of the two assemblages within the lagoon, with a duospecific assemblage in deeper water and a more diverse shallow water assemblage, is consistent with previous studies .…”
Section: Discussionsupporting
confidence: 86%
“…, Yassini and Jones, 1989, Yassini and Jones, 1995, Cotter, 1996, Nash et al, 2010 and internationally (e.g. , Goldstein, 1988, Patterson, 1990, Murray, 2013. The high relative abundance of a small number of taxa, irrespective of overall diversity, is consistent with previous estuarine foraminifera studies (Murray, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…Taldenkova et al [69] found this species to be more abundant in the upper bathyal Holocene of the Arctic Ocean than the latest Pleistocene, and ascribed it to a distal-river group of relatively deep-water species that thrive on slightly altered organic matter and is therefore restricted to areas with periodic delivery of organic matter. Murray [70] noted that M. baarleeanus has been recorded live in all oceans except the Indian Ocean. In ODP Hole 994C this species accounted for >0.02 of the CoBI t across six of the ten PATI boundaries, and was abundant in the early part of PATI-10 and in PATI-5 and PATI-4.…”
Section: Discussionmentioning
confidence: 99%
“…Lake (<2 mL L À1 : Diaz & Rosenberg 1995), despite a contemporary increase in nutrient input from the German Bight (Aure & Magnusson 2008) and simulated high primary productivity (Skogen et al 2004). Furthermore, the above-mentioned agglutinated fauna is strongly dominated by Eggerelloides medius, a species dependent on high-quality (fresh) organic matter and, hence, indicative of high primary productivity (Alve 2010;Murray 2013) rather than of oxygen depletion. The absence of severe oxygen depletion is supported by a relatively low abundance of low oxygen benthic foraminiferal fauna from c. 1700 years BP towards the present (Fig.…”
Section: Pollen-based T (°C)mentioning
confidence: 99%